2015
DOI: 10.1007/s11869-015-0349-0
|View full text |Cite
|
Sign up to set email alerts
|

Benzene, toluene, ethylbenzene and xylene concentrations in atmospheric ambient air of gasoline and CNG refueling stations

Abstract: This study aimed to assess workers' exposure to benzene, toluene, ethylbenzene, and xylene (BTEX) compounds in refueling stations of Ardabil city (Iran). Twenty-four refueling stations including 15 petrol and 9 compressed natural gas (CNG) stations from different regions were selected and monitored for ambient BTEX concentrations. Air samples were taken based on NIOSH Manual of Analytical Method no 1501. Target compounds were extracted using CS 2 and analyzed by GC equipped with FID. Average concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 34 publications
3
28
1
3
Order By: Relevance
“…A factor affecting the diurnal profile of benzene is time-dependent emissions in the vicinity of either gas stations (Kountouriotis et al, 2014; Rattanajongjitrakorn and Prueksasit, 2014) or heavily congested roadways (Correa et al, 2012; Kourtidis et al, 2002; Lin et al, 2011). In addition, the results of this study reveal that the average concentration of BTEX was more than other studies, specifically those conducted in the Tri-City area (Gdansk, Gdynia, Sopot), Poland (Marć et al, 2014), Ardabil, Iran (Hazrati et al, 2016b), and Gorakhpur, India (Masih et al, 2016). This can most likely be explained by the combination of heavy traffic, fuel quality standards, old cars, and vicinity to five gas stations in the sampling region of IKBT.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…A factor affecting the diurnal profile of benzene is time-dependent emissions in the vicinity of either gas stations (Kountouriotis et al, 2014; Rattanajongjitrakorn and Prueksasit, 2014) or heavily congested roadways (Correa et al, 2012; Kourtidis et al, 2002; Lin et al, 2011). In addition, the results of this study reveal that the average concentration of BTEX was more than other studies, specifically those conducted in the Tri-City area (Gdansk, Gdynia, Sopot), Poland (Marć et al, 2014), Ardabil, Iran (Hazrati et al, 2016b), and Gorakhpur, India (Masih et al, 2016). This can most likely be explained by the combination of heavy traffic, fuel quality standards, old cars, and vicinity to five gas stations in the sampling region of IKBT.…”
Section: Resultsmentioning
confidence: 51%
“…These findings are opposite of previous studies since benzene was the most abundant as compared to other components of BTEX in ambient air (Cerón-Bretón et al, 2015; Mohamed et al, 2002; Moolla et al, 2015; Mosaddegh Mehrjerdi et al, 2014; Srivastava et al, 2006). The mean values of benzene observed by Moolla et al (2015) (South Africa), Hazrati et al (2016a, 2016b) (Ardabil, Iran), Mosaddegh Mehrjerdi et al (2014) (Yazd, Iran), Mohamed et al (2002) (United States), Srivastava et al (2006) (Mumbai, India), and Cerón-Bretón et al (2015) (Monterrey, Mexico) were, 313.16, 1690, 1932, 18.94, 539.95, and 55.24μg/m 3 , respectively (Cerón-Bretón et al, 2015; Hazrati et al, 2016b; Mohamed et al, 2002; Moolla et al, 2015; Mosaddegh Mehrjerdi et al, 2014; Srivastava et al, 2006). A factor affecting the diurnal profile of benzene is time-dependent emissions in the vicinity of either gas stations (Kountouriotis et al, 2014; Rattanajongjitrakorn and Prueksasit, 2014) or heavily congested roadways (Correa et al, 2012; Kourtidis et al, 2002; Lin et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toluene, ethylbenzene and xylenes concentrations found in the air of the gas stations in this study did not exceed the limits stipulated by NIOSH and NR-15 (Table 2) Comparing the BTEX concentration levels obtained in this study with other cities in Brazil and the world (Figure 3), the values found these compounds were generally higher those obtained in Rio de Janeiro/Brazil [18], but much smaller those obtained in Bangkok/Thailand [15], Ardabil/Iran [20] and Murcia/Spain [35]. These variations can be attributed to differences in the composition of the fuels used in other countries, and the influence of seasonal and/or weather local factors.…”
Section: Concentrations Of Btex Compounds In the Air Of Gas Stations supporting
confidence: 43%
“…BTEX (benzene, toluene, ethylbenzene, and xylene) are common hazardous volatile organic compounds (VOCs) and toxic air pollutants emitted into the atmosphere from natural and artifi cial sources 1 . These compounds are widely used in industries, such as paint, printing, synthetic rubber and resin, detergent, ink and pesticides.…”
Section: Introductionmentioning
confidence: 99%